2022
DOI: 10.21203/rs.3.rs-1611980/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Essential oils of plants and their combinations as an alternative adulticides against Anopheles gambiae (Diptera: Culicidae) populations

Abstract: The persistence of malaria and the increasing of resistance of Anopheles gambiae species to chemicals remain major public health concerns in sub-Saharan Africa. Faced to these concerns, the search for alternative vector control strategies as use of essential oils need to be implemented. Here, the five essential oils (EOs) from Cymbopogon citratus, Cymbopogon nardus, Eucalyptus camaldulensis, Lippia multiflora, Ocimum americanum obtained by hydro distillation were tested according to WHO procedures on Anopheles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…gambiae (Balboné et al 2022b(Balboné et al , 2022c. In addition to their toxic effect shown recently by Balboné et al (2022bBalboné et al ( , 2022c, L. multi ora exerted an irritant effect on Anopheles and Aedes populations. That is useful in terms of its use in vector control strategies.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…gambiae (Balboné et al 2022b(Balboné et al , 2022c. In addition to their toxic effect shown recently by Balboné et al (2022bBalboné et al ( , 2022c, L. multi ora exerted an irritant effect on Anopheles and Aedes populations. That is useful in terms of its use in vector control strategies.…”
Section: Discussionmentioning
confidence: 80%
“…aegypti and An. gambiae, respectively (Balboné et al 2022b(Balboné et al , 2022c. On the other hand, studies conducted in Guinea Bissau, West Africa, had reported that O. americanum EO had also a repellent effect on Anopheles mosquitoes (Pålsson & Jaenson, 1999).…”
Section: Discussionmentioning
confidence: 99%